Effect of COVID-19 locked down on gender pay gap in Slovakia in the education sector - Róbert Modranský; Jakabová, Silvia; Michal Hanák (Technium Social Sciences Journal, 2020)
Presented paper deals with the gender pay gap in the public and private education sector as an indicator of gender inequality in the labor market and seeks its determinants in close connection with the declaration of a state locked down during the COVID 19 pandemic in Slovakia. In Slovakia, this pay gap has been, in the long term, one of the highest in the European union. Slovak women earn about 22 % less than men in average, which results in them being more threatened by poverty as well as achieving lower pensions. Sectors of labor market, where women predominate, are considered to be less prestigious and are associated with lower wages, the education sector is undoubtedly one of them. Career progress of women is made even more difficult by gender stereotypes and career breaks due to maternity and they are also more burdened with household care and childcare. Using the secondary analysis of data from the sample survey this paper analyzes the position of women in the labor market and the factors influencing the gender pay gap are examined by regression analysis. The decisive period of the analysis is considered to be the period March - May 2020, when a state locked down was declared in Slovakia in connection with the COVID 19 pandemic, which undoubtedly manifested itself in all sectors of the Slovak economy. The results show, that the gender pay gap is affected by the number of hours worked and education. However, it has also been shown, that the difference in education does not explain the gender pay gap since the gap is bigger between men and women with higher education than it is between men and women with secondary education.